Discurso político na charge - Cavalcanti, Cristiane Renata da Silva (2013)
This work focuses on discourse analysis of cartoons in the newspapers with a circulation of Pernambuco, O Globo and Folha de São Paulo, during the second round of the elections for President of the Republic of Brazil in 2010, from the theoretical methodological and Discourse Analysis. Its aim is to show how the effects of meaning of the charges are given from the relationship between the conditions of production (historicity) and discursive memory that, as an element, traverse the discursive object in their level of development of verbal/não- verbal nature and constitution, comprising well as discursive memory is important to understand the process of production of meaning in these discourses. As a starting point for creating the discursive corpus, we consider the major journalistic events of this period, which led us to cut for analysis only cartoons that circulated during the election campaign in the 2nd round of elections. The analysis focuses on the discovery that memories are mobilized in discourse chargístico and how they are involved in the mobilization of the senses and are essential to understanding Paraphrase and polysemic movements, producing other senses in these discursive practices. For recognition of the corpus, 12 were selected charges from three newspapers subdivided into thematic paths that were more evident in the media, in the period from 01 to 31 October 2010. We have seen throughout the analysis that the charges, although they occupy different places to say, parafrásticos produce meanings that guarantee the formation of a memory that holds the words, because there is only sense because had ever felt before, allowing it go up and sliding turning when in circulation in different producing the externality, which is present in the discourse, deriving other senses. Thus, we observe that the work assumes the perennial incompleteness of language, including the mean will always point drift to other senses. Then through the recollection of facts and speeches, materialized in words pictures, research can help to think of the importance of movement memories: discursive and social, that interferes with the production of meaning in charges.